Service Management Information System Web-Based Society on Siundol Jae Village Office - Khotnai Shinta; Raissa Amanda Putri (Budapest International Research and Critics University, 2022)
The community service system that is currently running in Siundol Jae village is still done manually, so that village services to the community are less effective and the community is also dissatisfied with village services. With the construction of a web-based community service management information system, it can make it easier for village officials to serve the community. The steps taken to design the system are data collection methods consisting of interviews, observations and literature studies. While the system development uses the waterfall method. From the results of this study, village officials can more easily provide services to the community and the community also does not have to wait long to get the letters they need.